Analisis Perancangan Sistem Jabatan Fungsional Pada UPT. Perlindungan Tanaman Pangan Dan Holtikultura Sumatera Utara - Nasyuwah S Hasibuan; Muhammad Ikhsan Harahap (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
This scientific work aims to provide understanding and knowledge to readers and researchers about how important it is to carry out system analysis and warfare in a field, especially in the Functional field in order to improve or improve the quality of a company or the field itself. System design is the depiction, planning, sketching of several separate elements in one complete and functioning unit. This research uses a qualitative approach with descriptive analysis method. The results of the research are that from several weaknesses obtained in the process of observing the system running in the UPT Finance Section - Food Crop Protection and Horticulture, a system development plan is needed. One way is by optimizing computer use, such as designing a desktop-based system to input data in real time and then improving data validation mechanisms and storage processes. A development plan that can be carried out using a computer will simplify the process of sending reports from the field easily and quickly.